On the relationship between black hole mass and X-ray variability amplitude in the low-mass regime of active galactic nuclei. Issue Volume 10:Issue S312(2014) (7th March 2016) - Pan, H.; Yuan, W.; Zhou, X.-L.; Dong, X.; Liu, B.
Abstract: Recent studies of active galactic nuclei (AGN) found a statistical inverse scaling between the X-ray normalized excess variance σrms 2 (variability amplitude) and the black hole mass spanning over M BH = 10 6 − 10 9 M ⊙ . We present a study of this relation by including AGN with M BH = 10 5 − 10 6 M ⊙ . It is found that the relation is no longer a simple extrapolation of the known inverse proportion, but starts to flatten around 10 6 M ⊙ . This behavior can be understood by the shape of the power spectrum density of AGN and its dependence on the black hole mass.